2017
DOI: 10.5301/jsrd.5000232
|View full text |Cite
|
Sign up to set email alerts
|

Digital Ulcers in Ssc Treated with Oral Treprostinil: A Randomized, Double-Blind, Placebo-Controlled Study with Open-Label Follow-up

Abstract: Prostacyclins are routinely used to treat vascular features of systemic sclerosis (SSc, scleroderma) but require parenteral infusion or inhalation. This study evaluated the safety and efficacy of oral treprostinil in digital ulcers secondary to SSc. Methods: This was a randomized (1:1) placebo-controlled, multicenter study in adults with SSc and at least one active digital ulcer at entry. Oral treprostinil was administered twice daily and titrated to maximum tolerated dose with clinical assessments at Weeks 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…One meta-analysis published in 2013 included, in addition to the two above-mentioned RCTs with intravenous iloprost, two additional RCTs, one with oral iloprost (100 or 200 µg/day vs placebo for 6 weeks) and one with oral treprostinil (slow release up to 16 mg two times a day for 20 weeks) 32 37 38. This analysis revealed a trend towards a beneficial effect of prostanoids over placebo for healing of DUs (the pooled risk ratio (RR); 95% CI) for number of patients with DUs improvement or healing: RR 1.33; 95% CI 0.97 to 1.84; p=0.08 38.…”
Section: Resultsmentioning
confidence: 99%
“…One meta-analysis published in 2013 included, in addition to the two above-mentioned RCTs with intravenous iloprost, two additional RCTs, one with oral iloprost (100 or 200 µg/day vs placebo for 6 weeks) and one with oral treprostinil (slow release up to 16 mg two times a day for 20 weeks) 32 37 38. This analysis revealed a trend towards a beneficial effect of prostanoids over placebo for healing of DUs (the pooled risk ratio (RR); 95% CI) for number of patients with DUs improvement or healing: RR 1.33; 95% CI 0.97 to 1.84; p=0.08 38.…”
Section: Resultsmentioning
confidence: 99%
“…Digital sympathectomy is a highly specialised procedure, performed only in specialist centres. Although a systematic review indicated that there is no good evidence base for surgical procedures (including sympathectomy) for RP [35], this is unsurprising given the small numbers of patients coming to surgery and the diffi culties inherent in running clinical trials of surgical procedures.…”
Section: Surgerymentioning
confidence: 99%
“…Oral PGs have been shown to be ineff ective in their current form [34]. A recent multicentre study of oral treprostinil in patients with systemic sclerosis-related digital ulcers [35] showed a small but statistically insignifi cant reduction in net ulcer burden…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Subjects receiving active drug achieved dose levels of approximately one‐half those achieved in trials in pulmonary arterial hypertension, in which titration was extended over 3 months. Similar limitations of dosing characterized the large trial of oral treprostinil for the RP‐related clinical complication of digital ischemic ulcerations, which also had negative results. Investigators in a past trial of oral iloprost for RP chose a fixed low dose based on estimates of tolerability .…”
mentioning
confidence: 85%